2021
DOI: 10.1186/s43055-021-00561-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion-weighted MRI in diagnosis and post therapeutic follow-up of colorectal cancer

Abstract: Background The colorectal cancer (CRC) is one of the deadliest cancers in the world. Local tumor stage, vascular or lymphatic invasion, and tumor grade are essential for accurate management. The main imaging modality for initial assessment and therapeutic response evaluation of CRC is magnetic resonance imaging (MRI). The purpose of this prospective study was to illustrate the role of diffusion-weighted MRI (DWI) and apparent diffusion coefficient (ADC) value in initial assessment and grading o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This is in agreement with a study on rectal polyps [21]. Other rectal MRI studies have shown similar results [15,22,23], but the literature is scarce on colonic tumors. We found…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in agreement with a study on rectal polyps [21]. Other rectal MRI studies have shown similar results [15,22,23], but the literature is scarce on colonic tumors. We found…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with a study on rectal polyps [21]. Other rectal MRI studies have shown similar results [15,22,23], but the literature is scarce on colonic tumors. We found no statistical difference in mADC values between N0 and N+ groups, and pT1-pT2 and pT3-pT4 groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pelvic MRI is used for the local of T and N staging of rectal cancer and has the advantage of improved patient comfort [542], improved reproducibility and accuracy [543], reduced care costs [544], and for completeness and better understanding of related pelvic anatomy [545][546][547]. The use of DWI with ADC value in addition to conventional MRI yields better diagnostic accuracy than using conventional MRI alone in detection, correlation with tumor histologic grade, and the initial staging in patients with locally advanced colorectal cancer [548,549]; however, DW-MRI is inferior to [F-18]-FDG-PET for the detection of primary lesions but superior for the detection of lymph node metastases [550]. MRI shows moderate sensitivity and good specificity for the detection of extramural venous invasion (EMVI) in colorectal cancer [551,552], while 3D colorectal MRI gives better and accurate segmentation results than 3D fully convolutional neural networks alone [553].…”
Section: Colorectal Cancermentioning
confidence: 99%